Interactions between Cenozoic tectonics and landscape dynamics in Londrina, Paraná, Brazil - Sowinski, Ana Cecília Branco; Salamuni, Eduardo; Santos, Marcilene dos; Calegari , Salomão Silva (Revista Brasileira de Geomorfologia, 2024)
The Londrina City, located in southern Brazil, is situated on the basalt of the Paraná Igneous Province (PIP), near tectonic structures such as the Guaxupé faults and the São Jerônimo-Curiúva and São Sebastião lineaments, with a history of reactivation in the Cenozoic. Between 2015 and 2018, low-magnitude earthquakes hit the municipality, suggesting a possible connection with these structures. This study investigates the relationship between Cenozoic tectonics and geomorphological dynamics, combining quantitative geomorphological analysis with field analysis of faults. The results reveal signs of tectonic control on the landscape, with two pulses of regional uplift/base level drop affecting the drainage network. Reactivated segments, especially at intersections of NE and NW structures, influence dynamics, with variations in uplift rates between basins and block rotation under a transtensive regime. Recent earthquakes are related to the reactivation of an N50-60E fault scarp, possibly the Guaxupé Fault, indicating recurrent tectonic movement. Paleostress analyses identify three deformation pulses, highlighting the complexity of landscape evolution in intraplate regions. These findings enhance understanding of regional tectonics, emphasizing the need to comprehend landscape evolution in interior plate areas, such as the South American Plate.